Social Portrait of a Pupil of the Simferopol Correctional Shelter for Minors (Late Xix - Early Xx Centuries) - Egorov, Dmitriy Olegovich (2020)
The article presents a multiple-criteria analysis of the composition of the Simferopol correctional shelter of the late XIX - early XX centuries. The social well-being of a child who showed elements of destructive behavior is assessed, the role of an educational institution in the life of juvenile delinquents is examined. The authors compiled a social profile of the pupil of the Simferopol correctional shelter, based on dominant indicators according to different criteria: the grounds for sending juvenile delinquents to the shelter, their age, the length of stay of juvenile offenders in the correctional institution, the family composition and literacy of the delinquent, religious and social status, place of residence, crimes committed, determining the definition of juvenile delinquents in a shelter, further life after release. The article analyzes the misconduct of foster children in a shelter and considers the system of punishment for juvenile delinquents.